Investigation of Uncertainties in Nonlinear Seismic Analysis of the Reinforced Concrete Shear Walls - Karaton, Muhammet; Osmanli, Omer Faruk; Gulsan, Mehmet Eren (Springer Int Publ Ag, 2021)
In this study, the use of the displacement-based fibre element (DBFE) method for modelling the nonlinear seismic response of reinforced concrete shear wall structures with a variation of damping ratios and types of structural damping is evaluated. The experimental seismic responses of the CAMUS I and NEES-UCSD shear wall structures are compared with nonlinear time-history analysis results obtained using the DBFE method. Comparisons are made in terms of the absolute maximum values of the top displacement, the base shear force, the base bending moment values and minimum differences between overlaps of top displacement time-history graphs. The Hilber-Hughes-Taylor-alpha integration method is selected for the dynamic solution algorithm. Recommendations are made for appropriate damping ratios for stiffness-proportional, mass-proportional, and Rayleigh damping to be used for the structural damping of nonlinear seismic analyses of the shear walls. The minimum difference between experimental and numerical analysis results is obtained less than 11% using Rayleigh damping. Additionally, the optimal number of fibre elements is researched with regard to the ratio of the mean length of the fibre elements to the longitudinal length of the shear wall. When the ratio is smaller than 3%, the differences between experimental and numerical analysis results for both shear walls are less than 2% at the optimal damping ratios.
Keywords: Shear wall structures; Displacement-based formulation; Nonlinear time-history analysis; Damping types; Fibre element number